Integration of a dissipative contact force model into vehicle–track dynamics for analysing wheel–rail dynamic interaction under short-wavelength irregularity. Issue 12 (2nd December 2022) - Ren, Dexiang; Tao, Gongquan; Yang, Xiaoxuan; Wen, Zefeng; Jin, Xuesong
Abstract : Wheel–rail dynamic interaction under short-wavelength irregularity which has a detrimental effect on the service life of vehicle and track components, is of crucial importance to be estimated accurately. Aiming at this, dissipative contact force models are integrated into a validated vehicle–track coupled dynamics model, which enables to consider the energy dissipation at the wheel–rail interface. Wheel–rail interactions for different dissipative contact force models are evaluated, and the Hu–Guo model is selected as the most suitable one for wheel–rail interaction analysis. The wheel–rail interactions for the Hu–Guo model and Hertz theory are analysed under different track irregularities including sinusoidal rail corrugation and rail welded joints. The simulation results indicate that the Hu–Guo model has little effect on the normal interaction at low frequencies, but reduces the contact force fluctuation amplitude obviously at high frequencies above 600 Hz, with a more significant reduction at the resonance peak of high frequency range. The Hu–Guo model has an obvious contact force phase lead compared with the Hertz theory at higher frequencies above 1250 Hz. The Hu–Guo dissipative contact force model is needed for the wheel–rail interaction analysis at high frequencies above 600 Hz.